2014
DOI: 10.1111/mmi.12753
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐dependent lipoylation of mitochondrial proteins in Plasmodium falciparum

Abstract: Summary Lipoate scavenging from the human host is essential for malaria parasite survival. Scavenged lipoate is covalently attached to three parasite proteins: the H-protein and the E2 subunits of branched chain amino acid dehydrogenase (BCDH) and α-ketoglutarate dehydrogenase (KDH). We show mitochondrial localization for the E2 subunits of BCDH and KDH, similar to previously localized H-protein, demonstrating that all three lipoylated proteins reside in the parasite mitochondrion. The lipoate ligase 1, LipL1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(62 citation statements)
references
References 57 publications
0
58
0
4
Order By: Relevance
“…LplA2 is partially redundant with LipB, and represents an alternate first step in the apicoplast lipoic acid synthesis pathway [84]. However, as LplA2 is also targeted to the mitochondrion [84] and required for the lipoylation of two enzyme complexes there [161], the enzyme appears to have multiple roles in lipoic acid metabolism.…”
Section: The Lipoic Acid Synthesis Pathwaymentioning
confidence: 92%
See 1 more Smart Citation
“…LplA2 is partially redundant with LipB, and represents an alternate first step in the apicoplast lipoic acid synthesis pathway [84]. However, as LplA2 is also targeted to the mitochondrion [84] and required for the lipoylation of two enzyme complexes there [161], the enzyme appears to have multiple roles in lipoic acid metabolism.…”
Section: The Lipoic Acid Synthesis Pathwaymentioning
confidence: 92%
“…The activity of PfLplA2 has been investigated using several approaches, and its function as a lipoate protein ligase is supported its ability to lipoylate the bacterial PDH when recombinantly expressed [83,161]. However, conflicting results for complementation and in vitro activity assays [83,84,161] suggest PfLplA2 is at best a poor lipoate protein ligase, and indicate its primary function is instead as an accessory to LplA1 in the mitochondrion [161].…”
Section: Lipoate Protein Ligase (Lpla2)mentioning
confidence: 98%
“…A, lanes 2–3). This is consistent with the previous observation that Pf LipL1 is unable to lipoylate the BCDH LD or KDH LD in a ligation reaction (Afanador et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Previous work showed that reduced lipoate is a requirement for the lipoylation of BCDH LD and KDH LD (Afanador et al ., ). Since Pf LipL2 catalyzed the attachment of lipoate, we hypothesized that Pf LipL2 only recognizes the reduced state of lipoyl‐AMP.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation